SOCIAL AND POLITICAL CHALLENGES IN THE PROTECTION OF CHILDREN IN ASYLUM AND DISPLACEMENT - Marjanovic, Milica (Political Review, 2023)
The paper indicates the position of refugee children and children of internally displaced persons in order to gain a better insight into the actual position of these two highly marginalized groups, with the aspiration for greater visibility in society, social engagement and social attention. Bearing in mind that in the case of these two groups, all aspects of life as a whole were primarily affected by forced migration as radical social changes, the main research focus will be on the consequences that are reflected on the population of child refugees and internally displaced persons. A secondary analysis of the content of the works of researchers who have dealt with this or a similar topic so far was used.
Keywords: children - internally displaced persons; children-refugees; socially vulnerable groups; social changes